STUDI KOMUNITAS FILUM MOLLUSCA DI ZONA INTERTIDAL PANTAI SUKAERLARAN DESA KENEBIBI KECAMATAN KAKULUK MESAK KABUPATEN BELU - Gonsianus Pakaenoni (KH. A. Wahab Hasbullah University, 2019)
The area which has recently received considerable attention is the coastal region / region. This is because the coastal region / region has a diverse wealth that can be utilized by the surrounding community as a source of the main food ingredients that are rich in animal protein content. Mollusca comes from Latin